2012
DOI: 10.1007/s00204-012-0979-z
|View full text |Cite
|
Sign up to set email alerts
|

AhR-mediated changes in global gene expression in rat liver progenitor cells

Abstract: Although the tumor-promoting effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), coplanar polychlorinated biphenyls (PCBs), and related compounds in liver tissue are primarily attributed to the activation of the aryl hydrocarbon receptor (AhR), the underlying molecular mechanisms are still unclear. Liver progenitor (oval) cells have been suggested to constitute a potential target for hepatocarcinogenic chemicals. To better understand AhR-driven pathways, we analyzed the transcriptional program in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 77 publications
2
25
0
Order By: Relevance
“…Transcriptome analysis of control or TCDD-treated rat liver cells revealed that TGF-b and Wnt signaling pathways were 2 of the most influenced pathways by AHR activation. 47 These data are intriguing and support our current study that orbital fibroblasts require AHR ligand-dependent activation of the AHR to attenuate b-catenin/Wnt signaling.…”
Section: Discussionsupporting
confidence: 79%
“…Transcriptome analysis of control or TCDD-treated rat liver cells revealed that TGF-b and Wnt signaling pathways were 2 of the most influenced pathways by AHR activation. 47 These data are intriguing and support our current study that orbital fibroblasts require AHR ligand-dependent activation of the AHR to attenuate b-catenin/Wnt signaling.…”
Section: Discussionsupporting
confidence: 79%
“…Formaldehyde promotes the formation of protein-protein and DNA-protein crosslinks [43], [44]. 2,3,7,8-tetrachlorodibenzo-p-dioxin, which is not directly genotoxic, binds to the aryl hydrocarbon receptor AhR, an intracellular protein that is a transcriptional enhancer affecting the expression of important genes [10], [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…The AHR-ARNT heterodimer binds to dioxin response elements (DREs) in the promoter region of downstream target genes and directly upregulates their expression [38]. Activated AHR is also capable of downregulating expression, and multiple studies have reported a larger number of genes being downregulated rather than upregulated following AHR activation [41,42,43,44,45,46,47]. However, it is less clear whether transcriptional downregulation is the result of AHR binding directly to the promoter, or if it is an indirect effect due to (1) AHR-induced upregulation of transcriptional inhibitors or (2) AHR-induced degradation of other transcriptional activators (discussed below).…”
Section: Ahr Signalingmentioning
confidence: 99%
“…The biological significance of these findings is not known. Microarray analysis of the multipotent stem cell-like cell line, WB-F344, after exposure to 3,3',4,4',5-pentachlorobiphenyl (PCB126, an AHR agonist) also found Wnt5a to be downregulated, along with Wnt4 , Fzd1 , and Fzd4 (Table 1 and Table 2) [47]. Numerous other genes linked to Wnt signaling were also downregulated including Lef1 and Axin2 .…”
Section: Effects Of Activated Ahr On Wnt Signalingmentioning
confidence: 99%